PRINSIP SELF-DETERMINATION SEBAGAI UPAYA PENYELESAIAN SENGKETA WILAYAH KASHMIR - Al Fath Putra Syafaat (2023)
The conflict in the Kashmir region has been going on for a very long time. The conflict has claimed many lives and destabilized the Kashmir region. Therefore, this conflict needs to be resolved peacefully. And in this paper, the efforts made are self-determination efforts. The self-determination effort will then be followed by a referendum. If you look at the history of the joining of Kashmir to India, then there is a legal flaw in the accession. In addition, according to various studies, the people of Kashmir prefer independence to join India or Pakistan. To understand how the principle of self-determination is in international law, this paper will discuss how it is regulated in international law. As well as how to implement these principles by conducting comparative studies with countries that have carried out self determination. And if Kashmir succeeds in holding a referendum and becoming a sovereign state, there will still be legal consequences that must be accepted. These consequences are related to the state's rights, obligations, and succession. Where in terms of succession will discuss the succession of goods, records, debts, and agreements. After doing this, there are still international obligations that Kashmir must carry out as a state, namely obtaining recognition to be part of the international community. The process of granting recognition is closely related to decisions that are political in nature from a country. So that it is possible not to recognize Kashmir as a sovereign state. And to improve Kashmir's situation, diplomacy is needed.